Entre o prescrito e o vivido : o PROEJA no Instituto Federal de Educação, Ciências e Tecnologia de Goiás-Campus de Formosa (2010-2015) - Brito, Roberta Gama (2017)
This dissertation is the result of a research that had the objective of analyzing the limits and the possibilities of implantation of the National Program of Professional Education Integrated to the Basic Education in the Modality of Young and Adult Education (PROEJA) in The Federal Institute of Education, Science and Technology of Goiás - Campus Formosa (IFGCampus Formosa) from 2010 to 2015. The case study was qualitative and guided by the approach of Historical-Dialectical Materialism. In the process of investigation were used different procedures for data collection: bibliographic research, documentary research, semistructured questionnaire applied to teachers working in PROEJA and the semi-structured interview technique with former managers of the Program. The results of the study pointed out that the implementation of PROEJA in the IFG-Campus Formosa followed the logic of schooling for work, since the orientation of the course offerings sought to meet the propositions of the ruling class that wants workforce to meet the new market's demands. Another issue highlighted in the research is the lack of spaces for dialogues/discussions in the Institution that prevent it's social agents from making moments of critical reflection on the proposals of the Program, especially in what concerns the understanding of the specificities of PROEJA, since this public educatonal policy presents innovative aspects regarding professional trainning integrated to basic education, particularly in what concerns the integrated curriculum. Facing, in this study, the limits and contradictions evidenced in the PROEJA's implementation process, it is proposed that the Institution take on the PROEJA policy, as a proposal of education capable of contributing, overcoming ideological obstacles and vertical management processes existent in the leading of public educational policies, as a way of proposing an alternative citizen education for all. In this sense, PROEJA's proposing entities need to really value EJA (young and adult education), based on the proposition of a policy that does not only contemplate pedagogical political principles which however, can offer objective material conditions for managers and teachers to have training, management and planning spaces that can contribute to the implementation of the policy in the institutional environment.